INSTITUTE OF THE STATE SERVICES IN KAZAKHSTAN AND ITS LEGAL OPOSREDOVANIYE - Baimahanov Мурат Таджи-Муратович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article covers factors that led to the need for a public services in Kazakhstan, shows haste and insufficient preparedness of the event, which resulted in a number of drawbacks. Legislative, governmental and departmental levels of legal regulation of the implementation of public services and the necessity of securing the rights and responsibilities of local government in the regulation of the relationship is considered.